Simple numerical methods of second- and third-order convergence for solving a fully third-order nonlinear boundary value problem - Dang, Quang A; Dang, Quang Long (Numerical algorithms, 2021)
In this paper, we consider a fully third-order nonlinear boundary value problem that is of great interest of many researchers. First, we establish the existence and uniqueness of solution. Next, we propose simple iterative methods on both continuous and discrete levels. We prove that the discrete methods are of second-order and third-order of accuracy due to the use of appropriate formulas for numerical integration and obtain estimate for total error. Some examples demonstrate the validity of the obtained theoretical results and the efficiency of the iterative methods.